Learning Vocabularies Using Short Stories at Primary School: Students’ Perception - Nazara, Pitriani (JET (Journal of English Teaching), 2019)
Various studies have shown that using short stories in language teaching is very advantageous because it provides authentic material, cultural enrichment, language advancement, and personal growth. Among the various literary genres, a short story is one of the most appropriate to use in a language classroom. This study was conducted to investigate the perception of primary school students to develop vocabulary. Employed a mixed methods research design, quantitative and qualitative data were collected from 30 sixth graders at Global Sevilla Primary School Jakarta. The quantitative data was collected using a questionnaire, and the qualitative data was gathered through interviews. The data obtained were descriptively analyzed employing SPSS and Excel. The results showed that the students' perception towards the use of short story was positive. For them, short stories were interesting materials to use to develop vocabulary. Based on findings, short stories are recommended to use to develop students' vocabulary.